The role of CB1 in intestinal permeability and inflammation. Issue 8 (19th September 2017) - Karwad, Mustafa A.; Couch, Daniel G.; Theophilidou, Elena; Sarmad, Sarir; Barrett, David A.; Larvin, Michael; Wright, Karen L.; Lund, Jonathan N.; O'Sullivan, Saoirse E.
ABSTRACT: The endocannabinoid system has previously been shown to play a role in the permeability and inflammatory response of the human gut. The goal of our study was to determine the effects of endogenous anandamide (AEA) and 2‐arachidonoyl glycerol (2‐AG) on the permeability and inflammatory response of intestinal epithelium under normal, inflammatory, and hypoxic conditions. Human intestinal mucosa was modeled using Caco‐2 cells. Human tissue was collected from planned colorectal resections. Accumulation of AEA and 2‐AG was achieved by inhibiting their metabolizing enzymes URB597 (a fatty acid amide hydrolase inhibitor) and JZL184 (a monoacylglycerol lipase inhibitor). Inflammation and ischemia were simulated with TNF‐α and IFN‐γ and oxygen deprivation. Permeability changes were measured by transepithelial electrical resistance. The role of the CB1 receptor was explored using CB1 ‐knockdown (CB1 Kd) intestinal epithelial cells. Endocannabinoid levels were measured using liquid chromatography–mass spectrometry. Cytokine secretion was measured using multiplex and ELISA. URB597 and JZL184 caused a concentration‐dependent increase in permeability via CB1 (P < 0.0001) and decreased cytokine production. Basolateral application of JZL184 decreased permeability via CB1 (P < 0.0001). URB597 and JZL184 increased the enhanced (worsened) permeability caused by inflammation and hypoxia (P < 0.0001 and P < 0.05). CB1 Kd cells showed reduced permeability response to inflammation (P < 0.01) but not hypoxia. 2‐AG levels were increased in response to inflammation and hypoxia in Caco‐2 cells. In human mucosal tissue, inflammation increased the secretion of granulocyte macrophage‐colony stimulating factor, IL‐12, −13, and −15, which was prevented with ex vivo treatment with URB597 and JZL184, and was inhibited by a CB1 antagonist. The results of this study show that endogenous AEA and 2‐AG production and CB1 activation play a key modulatory roles in normal intestinal mucosa permeability and in inflammatory and hypoxic conditions.—Karwad, M. A., Couch, D. G., Theophilidou, E., Sarmad, S., Barrett, D. A., Larvin, M., Wright, K. L., Lund, J. N., O'Sullivan, S. E. The role of CB1 in intestinal permeability and inflammation. FASEB J . 31, 3267–3277 (2017). www.fasebj.org